Integrity Systems in Malaysian Public Sector: An Empirical Finding - bin Abd Aziz, MA (2015)
Currently, governance in public administration has become a global issue as a result of the continuous stream of governance failures, fraud, inefficiency, corruption, and poor internal control and financial management. As such, the government of Malaysia has put an effort in term of programs and budgets in ensuring the public money being managed efficiently and with integrity. This study aims to assess the integrity systems of Malaysian Public Sector. Data were collected via questionnaires from 104 public officials from federal ministry in Malaysia. The data were collected based on the respondents' perception on twelve elements of integrity on practices in the department or agency by using seven-point Likert scale. Finding revealed that the mean score of each integrity items were above the mid-point. This has indicated that Malaysian Public Sector is serious in implementing the integrity concept in their daily management. The findings would provide further understanding for the Malaysian Public Sector to improve and enhance integrity system in the Malaysian Public Sector. (C) 2015 The Authors. Published by Elsevier B.V.